Emergency Medicine Providers' Knowledge and Management of Pediatric Tropical Diseases: A Needs Assessment. Issue 11 (November 2020) - Thomas, Vanessa A.; Crouse, Heather L.; Murray, Kristy O.; Hsu, Deborah C.; Camp, Elizabeth A.; Cruz, Andrea T.
Abstract : Objective: The aim of this study was to perform a needs assessment of pediatric (PEM) and general emergency medicine (EM) provider knowledge, comfort, and current practice patterns in the evaluation of pediatric tropical infectious diseases. Methods: An online survey was developed based on educational priorities identified by an expert panel via modified Delphi methodology. The survey included assessment of providers' typical evaluation, diagnosis, and treatment of tropical diseases and was distributed to PEM and EM providers in 2 large professional organizations. Results: A total of 333 physicians (285 PEM, 32 EM, 8 combined PEM/EM, and 8 general pediatricians in emergency department) participated. Fifty-five percent of vignettes were answered correctly. Those who trained outside the United States or Canada (odds ratio [OR], 1.8; 95% confidence interval [CI], 1.1–3.0) and PEM-trained providers (OR, 2.6; 95% CI, 1.2–5.9) were more likely to answer questions correctly. Providers answered more questions correctly about dengue (76%) and tuberculosis (77%) than typhoid (53%) and malaria (39%) (OR, 3.8; 95% CI, 3.0–4.9). Diagnostic evaluation for tropical diseases was variable with greater than 75% agreement for only 2 tests: blood smears in febrile patients from Africa (86%) and bacterial stool cultures in patients with bloody stools from Africa, Asia, or Latin America (94%). Providers had low (62%) or medium (35%) comfort level with pediatric tropical diseases, and 93% were interested in accessing emergency department–specific resources. Conclusions: Pediatric EM and EM providers' knowledge and evaluation for pediatric tropical diseases are variable. Providers recognized their knowledge gaps and expressed interest in gaining access to resources and guidelines to standardize and improve evaluation and treatment of these diseases. Abstract : Supplemental digital content is available in the text.